Ethics in engineering practice and research - Whitbeck, Caroline (Cambridge, UK. : Cambridge University Press, 2011)
'In this new edition of Ethics in Engineering Practice and Research, Caroline Whitbeck examines more scenarios of significant ethical problems in the engineering field'--
'The first edition of Caroline Whitbeck's Ethics in Engineering Practice and Research focused on the difficult ethical problems engineers encounter in their practice and in research. In many ways, these problems are like design problems: they are complex, often ill defined; resolving them involves an iterative process of analysis and synthesis; and there can be more than one acceptable solution. In the second edition of this text, Dr. Whitbeck goes above and beyond by featuring more real-life problems, stating recent scenarios, and laying the foundation of ethical concepts and reasoning. This book offers a real-world, problem-centered approach to engineering ethics, using a rich collection of open-ended case studies to develop skill in recognizing and addressing ethical issues'--
Machine generated contents note: Part I. Values and the Evaluation of acts in engineering: Introduction to ethical reasoning and engineering ethics; 1. Professional practice in engineering; 2. Two examples of professional behavior: Roger Boisjoly and William Lemessurier; Part II. Engineering Responsibility: 3. Ethics as design - doing justice to moral problems; 4. Central professional responsibilities of engineers; 5. Computers, software, and digital information; 6. Rights and responsibilities regarding intellectual property; 7. Workplace rights and responsibilities; Part III. Responsible research conduct: 8. Ethics in the changing domain of research; 9. Responsible authorship and credit in engineering and scientific research; Part IV. The future of engineering: 10. Responsibility for the environment; 11. End use and'macro' issues.
Includes bibliographical references and index.
Keywords: Engineering ethics